The branched‐chain amino acids valine and leucine have differential effects on hepatic lipid metabolism - Bishop, Christopher A.; Schulze, Matthias B.; Klaus, Susanne; Weitkunat, Karolin (The FASEB journal, 2020)
Dairy intake, as a source of branched‐chain amino acids (BCAA), has been linked to a lower incidence of type‐2‐diabetes and increased circulating odd‐chain fatty acids (OCFA). To understand this connection, we aimed to investigate differences in BCAA metabolism of leucine and valine, a possible source of OCFA, and their role in hepatic metabolism. Male mice were fed a high‐fat diet supplemented with leucine and valine for 1 week and phenotypically characterized with a focus on lipid metabolism. Mouse primary hepatocytes were treated with the BCAA or a Pparα activator WY‐14643 to systematically examine direct hepatic effects and their mechanisms. Here, we show that only valine supplementation was able to increase hepatic and circulating OCFA levels via two pathways; a PPARα‐dependent induction of α‐oxidation and an increased supply of propionyl‐CoA for de novo lipogenesis. Meanwhile, we were able to confirm leucine‐mediated effects on the inhibition of food intake and transport of fatty acids, as well as induction of S6 ribosomal protein phosphorylation. Taken together, these data illustrate differential roles of the BCAA in lipid metabolism and provide preliminary evidence that exclusively valine contributes to the endogenous formation of OCFA which is important for a better understanding of these metabolites in metabolic health.